Analysis of the significance and gender differences in the factors influencing antisocial behaviors among adolescents - Wenze Sui; Yan Gao; Liangyu Zhao; Yuke Yang; Lu Chen; Yining Hu; Xiangren Yi; Shuoqin Zhang; Sen Ma (Scientific Reports)
Abstract Adolescent antisocial behavior not only has an adverse effect on the healthy development of adolescents but also poses a threat to social order and public safety. The study included 18,470 high school students during the 2020–2023 school year as study participants. Random forest was used to assess the importance of influencing factors, and binary logistic regression analysis was conducted on the top eight identified factors. The study included 18,470 participants, consisting of 8867 boys and 9603 girls. The results showed that parents’ educational expectations (boys: OR = 0.942, girls: OR = 0.903) and smoking behavior (boys: OR = 1.055, girls: OR = 1.066) were common factors affecting antisocial behavior in both boy and girl adolescents. The number of good friends (OR = 1.122), current place of residence (OR = 1.039), and engage in regular physical activity (OR = 0.916) were specific influencing factors for boy adolescents’ antisocial behavior, while family economic conditions (OR = 1.092) was specific influencing factor for girl adolescents’ antisocial behavior. The study showcases Random Forest Model and the Logistic Model can effectively identify and analyze influencing factors, and the model performance is good. The identified influencing factors and their effects show gender differences. Therefore, we should formulate targeted prevention and improvement measures for adolescents’ anti-social behaviors.